EMOTIONAL AND COGNITIVE PROFILES OF INDIVIDUALS AFTER COVID-19: SYMPTOM DYNAMICS, GENDER DIFFERENCES, AND ADAPTATION RESOURCES (Psychology Travelogs, 2025)
The article presents the results of a study of emotional and cognitive changes in persons who have experienced the disease of COVID-19.A comprehensive assessment of the emotional state of persons who have suffered from COVID-19 was carried out, in retrospective and current dimensions, in order to identify the directions and severity of changes in depressive, anxiety and stress symptoms after the disease.The dynamics of emotional indicators before and after the transferred disease of COVID-19 in the general sample and taking into account the gender of the respondents were analyzed, using non-parametric criteria of statistical analysis.The peculiarities of subjective cognitive complaints in the post-epidemic period were studied according to the main cognitive domains (attention, memory, executive functions) and to determine their prevalence and intensity in the general sample and individual gender subgroups.A comparative analysis of subjective cognitive difficulties with objective indicators of cognitive functioning, obtained using a modified version of MoCA, was carried out in order to establish the specificity of the relationship between subjectively experienced and objectively fixed cognitive changes.The nature of relationships between indicators of emotional distress, subjective cognitive complaints and quality of life in the post-epidemic period was determined, as well as the role of psychological resilience as a potential adaptation resource was assessed.A comparative analysis of the current emotional, cognitive and resource state of men and women who have survived COVID-19 was carried out in order to identify the gender characteristics of the post-covid psychological response.Typical profiles of emotional and cognitive response in the post-covid period were determined based on the integration of the results of descriptive, comparative and correlation analyses, taking into account the level of emotional distress, severity of cognitive complaints, quality of life and resource potential of the individual
Keywords: post-covid condition; emotional distress; cognitive complaints; quality of life; psychological resilience; coping strategies; adaptation profiles